2016
DOI: 10.1007/s10900-016-0261-z
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Communication Channel Use and Health Information Source Preferences Among Latinos in Northern Manhattan

Abstract: Understanding key health concepts is crucial to participation in Precision Medicine initiatives. In order to assess methods to develop and disseminate a curriculum to educate community members in Northern Manhattan about Precision Medicine, clients from a local community-based organization were interviewed during 2014–2015. Health literacy, acculturation, use of Internet, email, and text messaging, and health information sources were assessed. Associations between age and outcomes were evaluated; multivariable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 16 publications
2
19
1
Order By: Relevance
“…11 Research examining the associations of demographic characteristics and socioeconomic status in the use of eHealth services found that people who were younger or had higher education levels were more likely than people who were older or had lower education levels to communicate with providers through electronic patient portals or emails. 7,[12][13][14][15][16][17] They were also more likely to acquire and track health information (eg, physician ratings and personal health records) on the internet. 13 Only a few studies examined racial/ethnic differences in the use of eHealth services, and the results were mixed.…”
mentioning
confidence: 99%
“…11 Research examining the associations of demographic characteristics and socioeconomic status in the use of eHealth services found that people who were younger or had higher education levels were more likely than people who were older or had lower education levels to communicate with providers through electronic patient portals or emails. 7,[12][13][14][15][16][17] They were also more likely to acquire and track health information (eg, physician ratings and personal health records) on the internet. 13 Only a few studies examined racial/ethnic differences in the use of eHealth services, and the results were mixed.…”
mentioning
confidence: 99%
“…Previous research with other Latino population groups suggests that acculturation level is an important influence on health information-seeking behaviour and preferred sources of health information. 63 64 More-acculturated individuals are more likely to seek health information and more likely to use electronic channels than less-acculturated individuals who are more likely to rely on social networks of friends for obtaining health information. 63 64 Our finding regarding Brazilian immigrant mothers’ low acculturation levels, combined with results of previous research suggests that successful interventions targeting Brazilian immigrant parents will require consideration of the target population’s acculturation levels.…”
Section: Discussionmentioning
confidence: 99%
“…Our initial steps included strategic partnering with a local non‐profit community‐based organization, the Northern Manhattan Improvement Corporation (NMIC) that serves the Washington Heights and Inwood communities of Upper Manhattan to first explore community constituent health concerns overall and specifically related to cancer, a topic previously found to be of concern to the community (Sepulveda‐Pacsi & Bakken, 2017). As our second step, we conducted an assessment of educational needs and learning preferences via quantitative surveys and focus groups among 497 adult community members (18+ years) accessing the services of NMIC, our community‐based organization partner (Hillyer et al, 2017). Of those who participated, 84.5% were foreign born, nearly 30% had inadequate health literacy, and 83.5% completed the survey in Spanish.…”
Section: Methodsmentioning
confidence: 99%
“…As our second step, we conducted an assessment of educational needs and learning preferences via quantitative surveys and focus groups among 497 adult community members (18+ years) accessing the services of NMIC, our community-based organization partner (Hillyer et al, 2017). Of those who participated, 84.5% were foreign born, nearly 30% had inadequate health literacy, and 83.5% completed the survey in Spanish.…”
Section: Preliminary Assessmentsmentioning
confidence: 99%
See 1 more Smart Citation